Color science and the visual arts a guide for conservators, curators, and the curious - Berns, Roy S. 1954- (The Getty Conservation Institute, 2016)
"Berns writes for two types of audiences: museum professionals seeking explanations to common color-related issues and students in conservation, museum studies, and art history programs. A unique feature of this book is the use of more than 200 images as its main medium of communication, employing color physics, color vision, and imaging science to produce visualizations throughout the pages. Engaging, incisive, and absolutely critical for any scholar or student interested in color science, this book is sure to become a key reference for the entire field." -- Provided by publisher